PEMBERDAYAAN MASYARAKAT PETANI TEMBAKAU DALAM MENINGKATKAN KESEJAHTERAAN DI DESA PANGTONGGAL KECAMATAN PROPPO KABUPATEN PAMEKASAN - Aang Kunaifi; Purnama Ningsih (Universitas Islam Tribakti (UIT) Lirboyo Kediri, 2025)
This community service project aims to empower tobacco farmers in Pangtonggal Village, Proppo District, Pamekasan Regency, to improve their economic well‑being and social resilience. The initiative was conducted using a Participatory Action Research (PAR) approach, involving farmers, local leaders, and researchers in identifying key issues, planning interventions, and implementing collaborative solutions. Activities included focus group discussions, training sessions, and mentoring in sustainable farming practices, post‑harvest processing, and marketing strategies. The results demonstrated increased knowledge and technical competencies among participants, strengthened group cohesion, and improved income-generating capabilities. Moreover, the participatory approach fostered trust and ownership within the farming community, making the outcomes more sustainable. This project highlights the significance of PAR as an effective method for addressing rural development challenges, especially in communities reliant on agriculture. It serves as a model for integrating local wisdom, community participation, and academic expertise to drive long‑term improvements in rural livelihood and well‑being.